2017
DOI: 10.1091/mbc.e17-05-0282
|View full text |Cite
|
Sign up to set email alerts
|

Membrane mechanics govern spatiotemporal heterogeneity of endocytic clathrin coat dynamics

Abstract: Cellular processes associated with spatiotemporal changes in membrane mechanics induce significant alterations in clathrin-mediated endocytosis dynamics. This phenomenon is also observed during morphological changes shaping embryo development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(63 citation statements)
references
References 37 publications
(55 reference statements)
3
58
0
Order By: Relevance
“…Clathrin dynamics were monitored in lateral epidermis and amnioserosa tissues of Drosophila embryos using the UAS/GAL4 system as described in ref. 38 . Drosophila embryos were gently pressed against the coverslip to position the apical surface of the lateral epidermis and amnioserosa cells within the evanescence field of the TIRF system.…”
Section: Tirf-sim Image Acquisitionmentioning
confidence: 99%
“…Clathrin dynamics were monitored in lateral epidermis and amnioserosa tissues of Drosophila embryos using the UAS/GAL4 system as described in ref. 38 . Drosophila embryos were gently pressed against the coverslip to position the apical surface of the lateral epidermis and amnioserosa cells within the evanescence field of the TIRF system.…”
Section: Tirf-sim Image Acquisitionmentioning
confidence: 99%
“…Plasma membrane tension is one of the most important determinants of endocytic clathrin coat structure and dynamics 19,[31][32][33][34] . Our automated analysis on genome edited SUM-159 cells expressing AP2-EGFP 35 revealed that average size of clathrin-coated pits increase when plasma membrane tension is elevated by hypo-osmotic shock ( Fig.…”
mentioning
confidence: 99%
“…Membrane-cytoskeleton adhesion enables the cytoskeleton to exert forces onto the plasma membrane. Hence, in-plane and cytoskeletal components of membrane tension are interdependent [23] and together they play a major role in regulating endocytosis [18,22,24,25] . Cellular processes associated with the creation of tension gradients can lead to spatio-temporal heterogeneity of endocytosis [8,16] .…”
Section: Membrane Tensionmentioning
confidence: 99%
“…Robust techniques to mechanically manipulate cells which are compatible with high-resolution microscopy, like cell stretchers, microcontact printing, stiffness tunable hydrogels, and micropillar arrays also gained progress in the last decade [12][13][14][15] . Automated algorithms for detecting and tracking endocytic events coupled with these sophisticated imaging techniques have enabled visualization of endocytosis in living organisms [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%